Diversity and distribution of scleractinian and non-scleractinian corals at selected areas in Tioman Island - Saad, Shahbudin; Khodzori, Mohd. Fikri Akmal; Yusof, Muhammad Hamizan (2014)
Diversity and distribution of Scleractinian and Non-scleractinian corals were investigated in Tioman Island (Teluk Benuang, Kampung Genting, Pulau Renggis and Teluk Teduh) using Coral Video Transect (CVT) method. A total of 30 genera belong to 13 families of Scleractinian and 2 families of Non-scleractinian corals were identified. The average percent coverage of coral family was dominated by Acroporidae (34.8%), followed by Faviidae (30.9%) and Poritidae (9.5%). The highest number of coral genera was found in Tlk. Benuang (24) compared to Tlk. Teduh (21), Pulau Renggis (19) and Kg. Genting (18). Based on Chi-square analysis, most of coral genera were found highly significance with the study areas (p<0.01) except Acropora, Hydnophora, Plerogyra, Cycloseris, Ctenactis, and Millepora. 10 m depth has the highest number of coral genera (29) compared to 5m depth (20). Analysis of Chi-square has shown that most of coral genera were found highly significance with depth (p<0.01) except Acropora, Hydnophora, Plerogyra, Pavona, Cycloseris, Ctenactis and Heliopora. Genus Acropora was found abundance in all study areas and depths. The Shannon-Weiner diversity index (H’) and Evenness index (EH’) of coral genera at Tlk. Benuang were 2.40 and 0.78, respectively. The Shannon-Weiner diversity index (H’) and Evenness index (Eh’) of coral genera at 10m depth were 2.75 and 0.80, respectively. Besides coastal development and high residential, the geographical, morphological and physico-chemical parameters were also the factors that influence the establishment of corals in Tioman. High sedimentation rate (1.91 ± 0.55 mg.cm-2.day-1), TDS value (34.5 ± 0.1 g/L), nitrate ( ) and ammonia concentration () recorded had contributed to less number of coral genera in Kg. Genting.